Suicidal ideation, attempt and associated factor among secondary school students in Harari regional state, Eastern Ethiopia. A multi-center cross-sectional study - Bete, Tilahun; Birhanu, Abdi; Negash, Abraham; Yadeta, Elias; Lemi, Magarsa; Balcha, Tegenu; Sertsu, Addisu; Birhanu, Bekelu; Nigussie, Shambel; Gemechu, Kabtamu; Meseret, Fentahun; Mohammed, Hanan; et al. (Frontiers in Psychiatry, 2023)
Background Suicide is a major public health issue across the globe. It is the second leading cause of death in adolescents. Even though the rate of suicide has increased, no study has been conducted to investigate the determinants of suicide in the study area. Therefore, this study aimed to assess the magnitude of suicidal ideation, suicide attempts, and its associated factors among secondary school students in the Harari regional state of Eastern Ethiopia. Methods An institutional-based cross-sectional study was conducted among randomly selected 1,666 secondary school students. A structured-self-administered questionnaire was used for data collection. The WHO Composite International Diagnostic Interview (CIDI) was used to assess suicidal ideation and suicide attempts. The Depression Anxiety and Stress Scale (DASS) was also used to assess depression, anxiety, and stress. Data were entered into EpiData version 3.1 and exported to Stata version 14.0 for the analysis. A logistic regression analysis was performed to determine the association between the outcome and independent variables and the statistical significance was declared at a p-value of < 0.05. Result The overall magnitude of suicidal ideation and attempts was 13.82% at 95% confidence interval (CI): 12.16–15.66 and 7.61% at 95% CI: 6.37–9.07, respectively. Suicidal ideations and suicide attempts were significantly associated with undergoing depressive symptoms (adjusted odds ratio [AOR]: 1.54; 95% CI: 1.08–2.19 and AOR: 2.37; 95% CI: 1.46–3.86, respectively), experiencing anxiety symptoms (AOR: 1.80; 95% CI: 1.25–2.59 and AOR: 1.89; 95% CI: 2.14–10.65, respectively), being exposed to sexual violence (AOR: 3.36; 95% CI: 1.65–6.84), and having a family history of suicidal attempts (AOR: 2.12; 95% CI: 1.21–3.69 and AOR: 4.74; 95% CI: 2.14–10.65, respectively), whereas living in a rural residence (AOR: 1.65 95%, CI: 1.08–2.55) was significantly associated only with suicide attempts. Conclusion and recommendations Nearly one in six secondary school students had both suicidal ideation and attempted to take their own life. Suicide is one of the psychiatric emergencies that need immediate action. Therefore, the concerned body from either a governmental or a non-governmental organization should work in setting strategies to minimize sexual violence as well as depressive and anxiety symptoms.